Removal of foreign bodies from the airways and esophagus development of the method and equipment over the centuries - Rybojad, Beata; Chudzik, Robert; Pawelec, Sławomir; Matuszewski, Piotr; Piróg, Paweł; Rybojad, Paweł (Journal of Education, Health and Sport, 2018)
The problem of aspiration of foreign bodies was already known in antiquity. The first described death of man was the case of the Greek poet Anakreon, who in 475 BC choked himself with a grape.Initially, the treatment was limited to the pneumonia caused by the presence of a foreign body, then treatment of surgical procedures was attempted.The first documented case of tracheotomy (known as bronchotomy) for removing a foreign body was described in 1717 by Verdue.Unfortunately there was a significant disadvantage of the devices used to remove foreign bodies from the airways and esophagus - lack of a proper light source. At the beginning doctors were using candles, but their light was insufficient to observe anatomical structures. Philipp Bozzini developed the first light source which allowed to view the upper part of the esophagus - He called it a "lichtleiter".However a milestone in the endoscopy was made by the French urologist Antonin Desormeaux. He presented an improved device, which he called the "endoscope". For this reason, he was hailed as "father of endoscopy". Nevertheless scientific and technical progress is still continuing. Doctors have at their disposal more and more modern equipment for the diagnosis and removal of foreign bodies from the airways and esophagus. But even the most perfect endoscope will not replace the doctor's skills combined with assurance of maximum safety during and immediately after the procedure.